Analysis of Agricultural Sub-Sectors Growth Rate Contribution to Agriculture’s Percent Share on Philippines’ GDP - Andrea Angela Mae M. Fernandez Fernandez; Ian Miguel M. Gersaniba Gersaniba; Winzel Jeilo Ng Tan Tan; Maria Antoinette L. Rosete Rosete (Faculty of Science and Technology University of Pramita Indonesia, 2022)
In this study, the researchers analysed how the agricultural sub-sectors contribute to the Philippines' overall agricultural sector percent share of GDP. The study employed time series data from 1980 to 2020 and was collected using secondary sources. The researchers will examine the data using The Ordinary Least Square (OLS) multiple regression analysis, Multicollinearity, and Normality Test. This study considered Agriculture's Percent Share of GDP as the dependent variable and several agricultural sub-sectors, such as crops, livestock, poultry, and fisheries growth rate, as the independent variables. Providing opportunities for local farmers by efficiently allocating government funds and subsidizing their production costs, creating policies emphasizing reducing environmental pollution, and improving the institutional and governance structures in the agricultural sector. The regression analysis of the data tested by the researchers indicates a positive and significant contribution to agriculture’s percent share to GDP of the Philippines. However, the results of livestock and poultry contribution to agriculture’s GDP was poor unlike crops and fisheries. This study recommends that Government of the Philippines should focus on all the agricultural sub-sectors to increase their growth rate contribution to the agriculture’s percent share to GDP. Investing into modern technological advancements is also recommended to strengthen the country’s agricultural sector.